The importance of copyright and shared norms for credit in Open Educational Resources - Norris, Meghan E.; Swartz, Mark; Kuhlmeier, Valerie A. (Frontiers in Education, 2023)
Open Educational Resources (OER) are reducing barriers to education while allowing creators the opportunity to share their work with the world and continue owning copyright of their work. To support new authors and adaptors in the OER space, we provide an overview of common considerations that creators and adaptors of OER should make with respect to issues related to copyright in the context of OER. Further, and importantly, a challenge in the OER space is ensuring that original creators receive appropriate credit for their work, while also respecting the credit of those who have adapted work. Thus, in addition to providing important considerations when it comes to the creation of open access works, we propose shared norms for ensuring appropriate attribution and credit for creators and adaptors of OER.